PENGEMBANGAN BAHAN AJAR FLIPBOOK MATERI PANTUN BERBASIS EXPERIENTIAL LEARNING - Nurusyifa, Risda; Kartikasari, Ratna Dewi (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
The background of this research is the lack of innovative and creative learning media that causes the students are less interested in learning. The aim of research is to make students to learn easier than before, producing new learning media and also increasing students' creativity in creating pantun. In this study, researchers developed flipbook teaching materials on experiential learning-based pantun material. The development of this teaching material contains students' personal experiences with what has happened to facilitate vocabulary when creating pantun. This research aims to produce a product, namely digital teaching materials to facilitate learning and encourage students to be more creative. The model used in this research is the ADDIE development model, which consists of Analysis, Design, Development of Production, Implementation and Evaluation. In this study, data obtained in the form of observations, interviews, media and material assessments with validation experts, and distributing questionnaires to students. In the results of the assessment stated a category that was very feasible to use in learning. Media experts get a feasibility percentage of 93.7%. The material expert received a feasibility percentage of 93.7%. For the feasibility of learner responses in the small trial class 85.5% got a feasibility percentage, while for the large class trial got a feasibility percentage of 89.7%. This flipbook teaching material can be used by educators and grade VII students in Indonesian language learning subjects. Keywords: pantun, flipbook, Experiential Learning.